Seasonal Adjustment Methods and the Determination of Turning Points of the EMU Business Cycle - Kirsten Lommatzsch; Sabine Stephan (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
In this paper, we investigate the impact of the adjustment for seasonal effects with different seasonal adjustment methods, the possible pre-treatment for calendar effects and the different order of aggregation and adjustment for the determination of the turning points of the European business cycle. The European business cycle is represented first by the GDP series (referring to the classical definition of a business cycle as fluctuations in the level of economic activity), and then by deviations from trend (which corresponds to the definition of the cycle as changing capacity utilisation). The turning points are determined using a mechanical procedure (Bry/Boschan methodology), which ensure that all series are treated alike. The comparison of turning points in the classical and growth cycles has brought the following results: 1.The order of seasonal adjustment and aggregation has only minor effects on the determined turning points of the European business cycle. 2.If the series are pretreated for calendar effects, turning points in the aggregated series can differ significantly. 3.It is not relevant whether the series were adjusted with a single method or with different methods (mixed aggregates).
Keywords: 330; Konjunktur; Aggregation; Konjunkturindikator; Statistische Methode; Eurozone; Schätzung; EU-Staaten; Saisonbereinigung